2011
DOI: 10.1088/2041-8205/727/2/l36
|View full text |Cite
|
Sign up to set email alerts
|

1.3 mm WAVELENGTH VLBI OF SAGITTARIUS A*: DETECTION OF TIME-VARIABLE EMISSION ON EVENT HORIZON SCALES

Abstract: Sagittarius A*, the ∼ 4 × 10 6 M ⊙ black hole candidate at the Galactic Center, can be studied on Schwarzschild radius scales with (sub)millimeter wavelength Very Long Baseline Interferometry (VLBI). We report on 1.3 mm wavelength observations of Sgr A* using a VLBI array consisting of the JCMT on Mauna Kea, the ARO/SMT on Mt. Graham in Arizona, and two telescopes of the CARMA array at Cedar Flat in California. Both Sgr A* and the quasar calibrator 1924−292 were observed over three consecutive nights, and both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
269
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(287 citation statements)
references
References 34 publications
17
269
1
Order By: Relevance
“…This trend is not reproduced by the other triangles, but the observed and simulated values show that the highest deviations from zero-closure phases occur for triangles with an angle of maximum resolution close to the position angle of the detected secondary component. Fish et al (2011) detected closure phase values of (0 ± 40) • for Sgr A* using mm-VLBI at 1.3 mm with an Earth-scaled triangle of SMT-JCMT-CARMA. Broderick et al (2011) showed that accretion flow models can reproduce closure phase values up to ±30 • in some cases.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This trend is not reproduced by the other triangles, but the observed and simulated values show that the highest deviations from zero-closure phases occur for triangles with an angle of maximum resolution close to the position angle of the detected secondary component. Fish et al (2011) detected closure phase values of (0 ± 40) • for Sgr A* using mm-VLBI at 1.3 mm with an Earth-scaled triangle of SMT-JCMT-CARMA. Broderick et al (2011) showed that accretion flow models can reproduce closure phase values up to ±30 • in some cases.…”
Section: Discussionmentioning
confidence: 85%
“…The short timescales suggest that this feature originates in a very compact region, possibly located close to the event horizon of the BH. Even though the detection of structures on these scales has not been achieved yet, Doeleman et al (2008Doeleman et al ( , 2009 and Fish et al (2011) have detected an intrinsic source structure of ∼40 µas on event-horizon scales using Very Long Baseline Interferometry (VLBI) at 0.7 mm and 1.3 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing VLBI observations at 1.3 mm (mm-VLBI, Doeleman et al 2008;Fish et al 2011) may be able to distinguish variabilities caused by magnetic turbulence and adiabatic expansion. In models based on relativistic MHD simulations, the size and shape of the emission region do not change with variations in the total flux.…”
Section: Millimeter Vlbi Signature Of Adiabatic Expansionmentioning
confidence: 99%
“…Source structure on event-horizon scales has been detected by Doeleman et al (2008) and Fish et al (2011) by means of very long baseline interferometry (VLBI) at 1.3 mm wavelength. In the radio and millimeter wavelength regime, SgrA* is found to be variable (Zhao et al 2003;Mauerhan et al 2005;Eckart et al 2008;Marrone et al 2008;Li et al 2009;Yusef-Zadeh et al 2008.…”
Section: Introductionmentioning
confidence: 99%